About polyanalytic functions of equal modulus - Zuyev, M. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: М. Ф. Зуев. О полианалитических функциях, равных по модулю M. Zujevas. Apie polianalizines funkcijas, lygias pagal modulį